Restrição alimentar parcial em juvenis de tambaqui (Colossoma macropomum) - THIAGO SANTANA COTRIM (2023)
Feed restriction is a practice used in fish production to optimize productivity and reduce production costs. However, the effects of partial feed restriction have not been fully elucidated. Therefore, the objective of this study was to assess the effects of partial feed restriction on zootechnical performance, health, carcass processing, bromatological composition, morphology of skeletal muscle tissue, and cellular structure of the intestine and liver in tambaqui (Colossoma macropomum) at the end of the restriction period and during the realimentation period. At the beginning of the experiment, the fish had an average weight and standard length of 168.7 g ± 9.40 g and 16.81 cm ± 0.40 cm, respectively, and were housed for 112 days in a recirculating water system (RWS). The experimental design was completely randomized and divided into three feeding management groups: control group, partial restriction 1 (PR1), and partial restriction 2 (PR2), with the fish rearing box considered as the experimental unit. The feeding management based on feeding rate for each treatment during 28 days was as follows: control group at 3.5% of live weight, PR1 at 1% of live weight, and PR2 at 0.5% of live weight. Subsequently, all treatment groups were subjected to a feeding rate of 3% of live weight for 56 days and then 2.5% of live weight for an additional 28 days. Biometric measurements were taken at five time points (day 0, 28, 56, 84, 112), and blood samples, hepatosomatic and visceral fat indices, muscle tissue, liver, and intestine samples were collected at three time points (day 0, 28, 112). At 28 days, the groups subjected to feed restriction showed poorer zootechnical performance (P<0.05), lower levels of cholesterol and triglyceride (P<0.05), and lower hepatosomatic and visceral fat indices compared to the control group (P<0.05), without altering the blood and histological variables of muscle, liver, and intestine. At 28 days, lower values of mineral matter and crude protein, and higher values of ether extract and gross energy were observed in the PR1 and PR2 groups compared to the Control. After 56 days of experimentation, the animals subjected to feed restriction showed higher weight gain efficiency and feed conversion, but their final weight was still lower than the control group. On day 84, only the PR2 group showed significant differences compared to the control group, displaying poorer performance in terms of final weight, total length, and standard length. The zootechnical performance in both restriction strategies was recovered at 112 days, regardless of the strategy used in the first 28 days. The biochemical variables, hepatosomatic indices, visceral fat, and bromatological composition also normalized during this period. There were no changes in body yield and hematological variables. Considering the total biomass, it was observed that the less severe restriction (1% of body weight) achieved similar results to the control group more quickly (day 84) compared to the more severe restriction (0.5% of body weight; day 112). It is concluded that reducing the feeding from 3.5% to 0.5% for 28 days (equivalent to an 85.7% reduction) is a viable and interesting strategy in several aspects for juvenile C. macropomum, without compromising their production, hypertrophic and hyperplastic behavior of skeletal muscle, and cellular structure of the liver and intestine, as long as a recovery period of 84 days is followed. Keywords: Compensatory growth, Blood parameters, Muscle growth, Feeding management.